2010
DOI: 10.2485/jhtb.19.123
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Study of Differential Expressions of Cytokeratin-13, -14, -17 and p53 in Epithelial Dysplasia and Carcinoma of the Tongue

Abstract: In cancers of the oral cavity, high histological malignancy grade is associated with higher risk of cervical lymph nodes, lung and bone metastases, which have great impact on the prognosis. Furthermore, early detection of these cancers is desirable so that treatment can aim at conserving oral functions and improving prognosis. It is known that several percent of leukoplakia that develop in the tongue become cancerous. Leukoplakia is a clinical diagnostic term, and histopathologically most cases show hyperkerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 19 publications
3
8
0
Order By: Relevance
“…Malignance marker p53 is a protein encoded by the TP53 tumor-suppressor gene, and is associated with apoptosis, the cell cycle, and genetic homeostasis 13) . Immunohistochemical expression of p53 is also mainly observed in the basal and parabasal cell layers, and its levels are increase depending on the severity of oral epithelial dysplasia, similarly to Ki-67 levels 15,16) .…”
Section: Discussionmentioning
confidence: 98%
“…Malignance marker p53 is a protein encoded by the TP53 tumor-suppressor gene, and is associated with apoptosis, the cell cycle, and genetic homeostasis 13) . Immunohistochemical expression of p53 is also mainly observed in the basal and parabasal cell layers, and its levels are increase depending on the severity of oral epithelial dysplasia, similarly to Ki-67 levels 15,16) .…”
Section: Discussionmentioning
confidence: 98%
“…Many studies have identified molecular markers for the pathological diagnosis or prognosis of oral atypical epithelium (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). For example, immunohistochemical detection of the proliferation marker Ki-67 and the squamous cell-differentiation markers cytokeratin 13 (CK13) and CK17 were reported to be useful for differentiating between OPL and reactive atypical epithelium (2,6,9,10,(15)(16)(17)(18)(19)(20)(21). CK13 is usually expressed in the normal oral epithelium but not in OPL, whereas CK17 is expressed in OPL, but not the normal oral epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, studies assessing the diagnostic or prognostic potential of molecular markers are limited. In these studies (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), the reliability of immunohistochemical scoring methods, the rationale for selecting certain cutoff points for defining sensitivity or specificity, and ascertainment of the independent contributory role(s) of each molecular marker to diagnosis or prognosis have been controversial. In this study, we sought to assess the diagnostic values of Ki-67, CK13, and CK17 for high-grade dysplasia by using logistic regression analyses.…”
Section: Introductionmentioning
confidence: 99%
“…However, the hypothesis that numerous immunohistochemical analyses are useful in the diagnosis of papillary-type cutaneous VC was confuted by the current study. CK13, 8 and 18 are reported to be useful markers in the diagnosis of squamous cell carcinoma in the head and neck region (13,15), and CK8 and 18 appear to be associated with the invasion and metastasis of squamous cell carcinoma (16). However, these CKs stained negatively in the neoplastic and surrounding healthy epidermal tissue of the present lesion, and, therefore, were not useful in the differential diagnosis of the present case.…”
Section: Discussionmentioning
confidence: 59%